2012
DOI: 10.1017/s1431927612001341
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characterization of Consolidant Products for Historical Renders: An Innovative Nanostructured Lime Dispersion and a More Traditional Ethyl Silicate Limewater Solution

Abstract: The conservation and durability of historical renders must be carried out through compatible techniques and materials. An important operation is the restitution of historical renders cohesion, turned friable by the loss of binder, usually due to physical and/or chemical actions. Surface consolidation is based on the use of materials with aggregating properties. This operation is reached usually through the application of organic or mineral consolidants, but inorganic consolidants are becoming preferred due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…These results highlight the importance of the material's pore structure in the effectiveness and penetration of the product. Other authors (Borsoi et al 2012;Costa et al 2012) observed insufficient nanolime penetration, no consolidation and nanolime migration back to the surface of the substrate in highly porous limestone, renders and mortars. Afterwards, it was verified that this phenomenon occurs during evaporation of the solvent (Borsoi et al 2015).…”
Section: Applicationsmentioning
confidence: 93%
“…These results highlight the importance of the material's pore structure in the effectiveness and penetration of the product. Other authors (Borsoi et al 2012;Costa et al 2012) observed insufficient nanolime penetration, no consolidation and nanolime migration back to the surface of the substrate in highly porous limestone, renders and mortars. Afterwards, it was verified that this phenomenon occurs during evaporation of the solvent (Borsoi et al 2015).…”
Section: Applicationsmentioning
confidence: 93%
“…Lower concentrated dispersions of Ca(OH) 2 NPs with a smaller size and higher homogeneity may correspond to a stronger consolidation effect . Lime mortars of reduced loss of cohesion can be treated only with nanolime or in combination with other consolidation products . In other cases, a larger number of applications or more concentrated dispersions is/are required.…”
Section: Alkaline Earth Metal Hydroxide Np Dispersionsmentioning
confidence: 99%
“…The latter is characterized by the loss of mechanical resistance, due to the deterioration of the binder-aggregate structure (Toniolo, et al, 2011;Borsoi, et al, 2012a). Mortar turns friable and susceptible to material loss by several degradation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Mortar turns friable and susceptible to material loss by several degradation processes. The presence of water or high humidity, salts crystallization, action of environmental agents or occurrence of chemical phenomena can lead to cohesion loss (Toniolo, et al, 2011;Borsoi, et al, 2012a). The recovery of the cohesion is achieved with the application of consolidating products that penetrate in the mortar porous structure and restore the connections of the binder-aggregate system, enhancing the preservation of the original materials.…”
Section: Introductionmentioning
confidence: 99%